Marketing performance : how marketers drive profitable growth - Bauer, Thomas; Freundt, Tjark; Gordon, Jonathan; Perrey, Jesko; Spillecke, Dennis (John Wiley & Sons, 2016)
A hands-on guide to better marketing for top managers, this book delivers expert insight, a wealth of proven success factors, and real-life case studies that will help you drive marketing performance and grow your business. --